High‐accuracy voltage regulation method for PV distribution systems. Issue 10 (1st May 2019) - Zhang, Zhanqiang; Dou, Chunxia; Yue, Dong; Zhang, Bo
Abstract : In this Letter, a novel voltage regulation method is proposed for ensuring voltage security in photovoltaic (PV) distribution systems. It is a two‐level regulation to reduce overall voltage deviation (VDE) and voltage difference (VDI). Firstly, evaluation indexes for VDE and VDI are built. Then, in order to reduce VDE, primary regulation by sensitivities‐based power compensation is developed. Furthermore, in order to reduce VDI, secondary regulation by using PI coordinate compensator is built. Compared with other methods, the proposed method can achieve high regulation accuracy. The effectiveness is verified in a PV platform.